1989
DOI: 10.1111/j.1468-5957.1989.tb00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments For ‘Extraordinary Items’In Smoothing Reported Profits of Listed Australian Companies: Some Empirical Evidence

Abstract: Nothing is more likely to undermine the credibility of financial reporting than the suspicion that the results reported were predetermined and that the accounting methods used were selected to produce the results desired by the preparers of the report', Solomons (1983).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Barnea et al (1976) examined managers' discretionary use of certain revenue and expense items that could be classified as either ordinary or extraordinary in order to determine whether managers engaged in 'classificatory smoothing'. The authors stated that the results they obtained strongly support 'the hypothesis that managements behave as ;f they smoothed income before extraordinary items (both before and after fixed charges) through the accounting manipulation of extraordinary items' (p. 117).4 Craig and Walsh (1989), citing the tremendous flexibility that managers of Australian companies have in reporting EIs, examined a sample of Australian companies for evidence that EIs are used to align reported earnings with expected earnings. Their results showed that the largest companies in the 84-firm sample exhibited evidence of income smoothing through the use of EIs.…”
Section: Introductionmentioning
confidence: 65%
“…Barnea et al (1976) examined managers' discretionary use of certain revenue and expense items that could be classified as either ordinary or extraordinary in order to determine whether managers engaged in 'classificatory smoothing'. The authors stated that the results they obtained strongly support 'the hypothesis that managements behave as ;f they smoothed income before extraordinary items (both before and after fixed charges) through the accounting manipulation of extraordinary items' (p. 117).4 Craig and Walsh (1989), citing the tremendous flexibility that managers of Australian companies have in reporting EIs, examined a sample of Australian companies for evidence that EIs are used to align reported earnings with expected earnings. Their results showed that the largest companies in the 84-firm sample exhibited evidence of income smoothing through the use of EIs.…”
Section: Introductionmentioning
confidence: 65%
“…It is important to note that the bigger the company is, the higher its political costs will likely be. Therefore, bigger companies should be more inclined to use income smoothing because they are more visible socially and under the eye of the government and the general public (Chalayer, 1994;Craig & Walsh, 1989;Iñiguez & Poveda, 2004;Michelson et al, 1995Michelson et al, , 2000Moses, 1987).…”
Section: H (02)mentioning
confidence: 99%
“…Such ratios are usually a poor guide to future financial prospects. The numerators and denominators of such ratios are calculated from information emerging from the application of an oftentimes counter-intuitive and bizarre set of rules which produce measures lacking in any reasonable sense of contemporary monetary equivalence ( ) Chambers, 1973;O'Connor, 1973;Bird & McHugh, 1977 . The Guide is based on an outdated, largely discredited view of the role and usefulness of conventionally-prepared published financial statements and the extent to which those statements reflect current market ( measures; have information content, even narrowly-defined Ball & Brown, ) 1968;Beaver, 1968 ; are the product of earnings management and dis-( cretionary accounting policy choice Beidleman, 1973;Eckel, 1981;Worthy, ) 1984;Craig & Walsh, 1989;Merchant & Rockness, 1994, among others ; ( ) indulge in '' foozles'' and feral accounting Clarke et al, 1997 andbig ( bath accounting Greene, 1986;Weberman, 1986;Elliott & Shaw, 1988; ) Walsh et al, 1991 and adopt other dubious and highly idiosyncratic practices. Many of these limitations are captured in the various critiques ( of accounting offered over the years, most prominently by Briloff 1972 Thus, reading the IBM Guide is like being put in a time warpᎏ in a ''cone of ignorance''.…”
Section: Technical and Rhetorical Featuresmentioning
confidence: 99%